FACTORS AFFECTING THE EFFICIENCY AND SUSTAINABILITY OF SMALL INDUSTRIAL ENTERPRISES (British Journal of Global Ecology and Sustainable Development, 2025)
The article highlights the issues of enhancing the competitiveness of small business entities under market economy conditions, efficient use of resources, implementation of innovative technologies, and improvement of labor productivity. It also examines external and internal factors determining production efficiency, government support policies, and the social conditions of enterprise employees.